Etika Administrasi Publik Pilar Utama Kepercayaan Masyarakat - Taufiqurokhman, Taufiqurokhman; Rossa, Zalfa Zafirah (Universitas Medan Area, 2025)
The enactment of Law of the Republic of Indonesia Number 30 of 2014 concerning Government Administration emphasizes the importance of transparent, accountable, and equitable public administration services. This research is essential to strengthen the application of ethical principles in public administration as a basis for creating quality and reliable services. This research aims to identify factors that influence the application of ethics in public administration and formulate strategies to improve compliance with these ethical standards. The research method systematically uses a qualitative approach with literature studies, through data collection from journals, books, and indexed scientific works. The study results indicate that leadership factors, organizational culture, strict regulations, and active community participation influence the application of ethics. These findings conclude that an ethical approach can strengthen integrity, expand accountability, and encourage community involvement in public decision-making. The implications of these findings emphasize that ethics-based public administration can produce more representative, fair, and widely accepted policies. This research makes an important contribution to developing public administration literature and offers practical guidance to encourage ethics-based bureaucratic reform in Indonesia.